Silver-Cobalt bimetallic nanoparticles to the generation of hydrogen from formic acid decomposition - Elham Shafik Aazam; Zoya Zaheer (Arabian Journal of Chemistry, 2022)
The fabrication of cost effective heterogeneous catalysts for the release of hydrogen from hydrogen storage materials is the key technological challenge to the fuel-cell based hydrogen economy. Ag-Co bimetallic NPs were fabricated by using sodium dodecyl sulphate (SDS) and sodium borohydride as stabilizing and reducing agents, respectively. Catalytic activity of SDS-Ag-Co was higher than that of SDS free Ag-Co and monometallic (Ag and Co) due to the electron interactions and synergistic effect between the Ag and Co. Ag10-Co90 exhibited the superior catalytic activity, with rate constant of 5.2 × 10−4 s−1 at 303 K, activation energy of 46 kJ/mol, activation enthalpy of 44 kJ/mol, activation entropy of −165 J/K/mol, and turn over frequency of 240 h−1. The hydrogen generation rate increased and decreased with in increasing temperature, molar concentration of formic acid, presence of sodium formate, and pH, respectively. The kinetic rate equation can be stated as: rate = -d[formic acid]/dt = kobs[formic acid]0.99[Ag50Co50]0.98, kobs = 2.48 × 107 exp (−5637.96/RT).